2020
DOI: 10.1128/aac.00825-20
|View full text |Cite
|
Sign up to set email alerts
|

Atazanavir, Alone or in Combination with Ritonavir, Inhibits SARS-CoV-2 Replication and Proinflammatory Cytokine Production

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is already responsible for far more deaths than previous pathogenic coronaviruses (CoVs) from 2002 and 2012. The identification of clinically approved drugs to be repurposed to combat 2019 CoV disease (COVID-19) would allow the rapid implementation of potentially life-saving procedures. The major protease (Mpro) of SARS-CoV-2 is considered a promising target, based on previous results from related CoVs with lopinavir (LPV), an HIV protease inhibitor.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 50 publications
5
105
1
3
Order By: Relevance
“…These results agree with previous reports in which HIV protease inhibitors lacked detectable activity against 3CL pro in vitro [ 18 , 19 , 20 ]. In contrast, other early studies found that some HIV protease inhibitors block SARS-CoV-2 replication in cell culture [ 35 , 36 , 37 ]. However, Hattori and co-workers recently demonstrated that these findings were likely false positives due to compound cytotoxicity [ 38 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These results agree with previous reports in which HIV protease inhibitors lacked detectable activity against 3CL pro in vitro [ 18 , 19 , 20 ]. In contrast, other early studies found that some HIV protease inhibitors block SARS-CoV-2 replication in cell culture [ 35 , 36 , 37 ]. However, Hattori and co-workers recently demonstrated that these findings were likely false positives due to compound cytotoxicity [ 38 ].…”
Section: Discussionmentioning
confidence: 86%
“…Human immunodeficiency virus (HIV) protease inhibitors, particularly lopinavir and nelfinavir, have been reported to inhibit the replication of SARS-CoV-2 in cell culture [ 35 , 36 , 37 ]. However, other groups have reported that HIV protease inhibitors do not block SARS-CoV-2 3CL pro in vitro, even at the maximal concentration tested (20 or 100 µM) [ 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…For animal experimentation, appropriate BSL-3 platforms are even more rare. In Brazil, for instance, the laboratories that excelled at generating relevant and important knowledge during epidemics of Zika, dengue and Chikungunya have had to face long waiting lines to access BLS-3 facilities in their own or collaborating institutions [ 5 , 6 ] (preprints: [ [7] , [8] , [9] , [10] , [11] ]). Ultimately, this has had the effect of concentrating the ability to advance the preclinical development of vaccines and antivirals to the richest countries.…”
Section: Biosafety Level Requirements During Epidemicsmentioning
confidence: 99%
“…Atazanavir and fluvoxami,ne for example, include both pharmacogenetics information and prescription recommendations. A molecular dynamics analysis and in vitro experiments showed that atazanavir, a protease inhibitor against human immunodefiency virus (HIV), could inhibit SARS-CoV-2 replication, alone or in combination with ritonavir 9 . Atazanavir inhibits the hepatic uridine diphosphate glucuronosyltransferase family 1 member A1 (UGT1A1), thereby preventing the glucuronidation and elimination of bilirubin 10 .…”
Section: Introductionmentioning
confidence: 99%